Mechanical Bowel Obstruction Caused by Incarcerated Left Amyand’s Hernia with Acute Appendicitis in Children - Muhammad Zaki Abdul Hafiz; Jon Efendi; Budi Pratama Arnofyan (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Amyand’s hernia is rare condition defined as the inclusion of the appendix in an ingunal hernia sac, It is an uncommon and rare condition estimated to be found in approximately 1 % of hernia. However, in just 0.08 %, the condition is complicated by an acute appendicitis. It may present as a tender inguinal or inguinoscrotal swelling. In patients presenting amyand’s hernia with mechanical bowel obstruction, signs of acute appendicitis may not be initially recognized. This was the case while our patient was in surgery, as signs suggestive of acute appendicitis were discovered and the patient received appendectomy and herniotomy. Presently, We report a case of Amyand’s hernia in a 9-month-old male, who presented as a left-sided congenital hernia with distended abdominal and pain in the left groin. He underwent appendectomy and herniotomy, which revealed that the hernia sac containing elongated inflamed appendix appeared with some adhesions to sac, lying in the inguinal canal.